EV-A71 invades the central nervous system and affects the blood-brain barrier in a tree shrew model - Wang, Wen-Guang; Wang, Xuan; Li, Na; Kuang, De-Xuan; Tong, Pin-Fen; Lu, Cai-Xia; Han, Yuan-Yuan; Sun, Xiao-Mei; Dai, Jie-Jie; Liu, Long-Ding (Frontiers in Immunology, 2025)
IntroductionThe enterovirus A71 (EV-A71)-caused central nerve system (CNS) damage seriously endangers the health of infants and young children, but the underlying mechanisms by which EV-A71 crosses the blood-brain barrier (BBB) are still largely unknown. This study developed a tree shrew (Tupaia belangeri) model to examine EV-A71 neurotropism and the disruption of the BBB.MethodsA cohort of twenty-two tree shrews, aged three months, were inoculated intranasally and orally with EV-A71 to establish an in vivo infection model. Complementary in vitro experiments were conducted using primary brain microvascular endothelial cells (MVECs) and astrocytes (AS) isolated from tree shrews.ResultsTree shrews infected with EV-A71 demonstrated symptoms of fever, vesicular lesions, and sustained viremia. Viral replication was observed in neural tissues, including the brain and spinal cord, as well as in select non-neural organs, accompanied by histopathological changes. Evans blue permeation assessment showed increased BBB permeability. EV-A71 infection down-regulated tight junction proteins Claudin-5 and junctional adhesion molecule A in the brain. In vitro studies showed that EV-A71 replicated efficiently in MVECs and AS, inducing cytopathic effects. Scavenger Receptor Class B Member 2 (SCARB2) and Annexin A2 (ANXA2) were identified as potential functional receptors facilitating viral entry. EV-A71 infection led to the dysregulation of tight junction proteins, matrix metalloproteinases, and Major facilitator superfamily domain-containing protein 2a. EV-A71 also stimulated the immune activity of AS.DiscussionThis study indicated that SCARB2 and ANXA2 play a role in the invasion of EV-A71 into the CNS of tree shrews. EV-A71 infection down-regulated tight junction proteins and increased the BBB permeability. This model provides a novel platform for studying EV-A71 neuropathogenesis.